Nonthermal Microwave Effects Revisited: On the Importance of Internal Temperature Monitoring and Agitation in Microwave Chemistry - Herrero, M. Antonia; Kremsner, Jennifer M; Kappe, C. Oliver (Journal of organic chemistry, 2008)
The concept of nonthermal microwave effects has received considerable attention in recent years and is the subject of intense debate in the scientific community. Nonthermal microwave effects have been postulated to result from a direct stabilizing interaction of the electric field with specific (polar) molecules in the reaction medium that is not related to a macroscopic temperature effect. In order to probe the existence of nonthermal microwave effects, four synthetic transformations (Diels−Alder cycloaddition, alkylation of triphenylphosphine and 1,2,4-triazole, direct amide bond formation) were reevaluated under both microwave dielectric heating and conventional thermal heating. In all four cases, previous studies have claimed the existence of nonthermal microwave effects in these reactions. Experimentally, significant differences in conversion and/or product distribution comparing the conventionally and microwave-heated experiments performed at the same measured reaction temperature were found. The current reevaluation of these reactions was performed in a dedicated reactor setup that allowed accurate internal reaction temperature measurements using a multiple fiber-optic probe system. Using this technology, the importance of efficient stirring and internal temperature measurement in microwave-heated reactions was made evident. Inefficient agitation leads to temperature gradients within the reaction mixture due to field inhomogeneities in the microwave cavity. Using external infrared temperature sensors in some cases results in significant inaccuracies in the temperature measurement. Applying the fiber-optic probe temperature monitoring device, a critical reevaluation of all four reactions has provided no evidence for the existence of nonthermal microwave effects. Ensuring efficient agitation of the reaction mixture via magnetic stirring, no significant differences in terms of conversion and selectivity between experiments performed under microwave or oil bath conditions at the same internally measured reaction temperatures were experienced. The observed effects were purely thermal and not related to the microwave field.